Early childhood mortality and affecting factors in developing countries: an experience from Bangladesh - Kabir, M.A.; Al-Amin, Abul Quasem; Alam, Gazi Mahabubul; Matim, M.A. (Asian Network for Scientific Information, 2011)
Within a method of a cross-sectional survey that adopts following as key variables i.e., demographic, socio-economic and health-care factors, thisstudy aimed to understand early childhood mortality rate and probable reasons in Bangladesh. In order to have probable rationality "logistic regression" of "multivariate statistical" technique is used to figure out the factors that are responsible for childhood mortality. The women who were married in the range of ageing 10-49 were asked to provide complete history about their "giving birth" for the reference period of 5 years. Statistical findings state that the rate of "national", "infant" and "under five year mortality" is, respectively 286, 461 and 525. Multi-examined statistical investigations sum up that "preceding birth interval", "birth order" and "number of living children" are significantly affect early childhood mortality. In addition, with the functionality of socio-economy, mother's education, source of drinking water and hygienic sanitation have also a significant impact on the rate of children mortality. Moreover, exposures to mass media, healtcare facilities have positive impact. Results also indicate that mothers who are more aware about helathcare are likely to be less mortality experience than their unaware counterparts.